Wnt, Notch, and TGF-β Pathways Impinge on Hedgehog Signaling Complexity: An Open Window on Cancer - Pelullo, Maria; Zema, Sabrina; Nardozza, Francesca; Checquolo, Saula; Screpanti, Isabella; Bellavia, Diana (Frontiers in Genetics, 2019)
Constitutive activation of the Hh signalling pathway is associated with increased risk of developing several malignancies. The biological and pathogenic importance of Hh signalling emphasizes the need to control its action tightly, both physiologically and therapeutically. Evidence of crosstalk between Hh and other signalling pathways is reported in many tumour types. Here, we provide an overview of the current knowledge about the communication between Hh and major signalling pathways, such as Notch, Wnt and TGF/β, which play critical roles in both embryonic and adult life. When these pathways are unbalanced, impaired crosstalk contributes to disease development. It is reported that more than one of these pathways are active in different type of tumours, at the same time. Therefore, starting from a plethora of stimuli that activate multiple signalling pathways, we describe the signals that preferentially converge on the Hh signalling cascade that influence its activity. Moreover, we highlight several connection points between Hh and Notch, Wnt or TGFβ pathways, showing a reciprocal synergism that contributes to tumorigenesis, supporting a more malignant behaviour by tumour cells, such as in leukaemia and brain tumours. Understanding the importance of these molecular interlinking networks will provide a rational basis for combined anticancer drug development.